Sosialisasi Poster Anemia Pada Kehamilan Di Puskesmas Kotabaru - Dameria Tambun; Hartinah Hartinah; Ika Friscila; Aida Fitriani (Jurnal Pengabdian Bidang Kesehatan, 2024)
Complications that can occur during pregnancy. The impact of these complications is that mothers who have given birth are likely to experience problems after giving birth. Anemia is a serious global health problem, especially in developing countries, with estimates that 30% of the world's population suffers from this condition. This problem is mainly found in teenagers and pregnant women. The aim of this service activity is to socialize posters about anemia in pregnancy at the Kotabaru Community Health Center. Community service activities will be carried out in January 2024 in the working area of the Kotabaru Community Health Center. Participants in this activity were midwives, cadres, pregnant women, husbands, and community representatives in the Kotabaru Community Health Center working area. The results of community service activities to socialize posters on anemia in pregnancy at the Kotabaru Community Health Center are that the activities have been carried out with active participation from participants in the socialization activities, including midwives, cadres, pregnant women, husbands and community representatives in the working area of the Kotabaru Community Health Center.